Anaerobic digestates grown oleaginous microalgae for pollutants removal and lipids production. (December 2022) - Tan, Xiao-Bo; Zhang, Ya-Lei; Zhao, Xian-Chao; Yang, Li-Bin; Yangwang, Shun-Cheng; Zou, Yue; Lu, Jue-Ming
Abstract: Anaerobic digestates were potential mediums for cultivating oleaginous microalgae, but their various components brought uncertainties for aglal growth and lipids production. In this study, three microalgae strains were tested to grow on four typical anaerobic digestates. The results showed that anaerobic food wastewater was an optimal medium for C. pyrenoidosa and S. obliquus culture ( N. oleoabundanst cannot survive), achieving the highest biomass (2.15–2.32 g L −1 ) and lipids production (20.6–32.5 mg L −1 ·d −1 ). In contrast, three microalgae strains could grow suboptimally in anaerobic municipal (0.79–0.95 g L −1 ) and toilet (0.92–1.40 g L −1 ) wastewater, but showed poor performances in anaerobic swine wastewater. The growth of microalgae removed 40.9–63.4% of TOC, 83.7–96.3% of NH4 + -N and 70.3–89.4% of TP in the three ADs. In addition, it was unfortunately found that the lipids content and saturation degree in fatty acids significantly decreased in ADs with sufficient nutrients. It suggests that some measures should be taken to balance biomass, lipids production and quality for cultivating microalgae in anaerobic digestates. Graphical abstract: Image 1 Highlights: Oleaginous microalgae successfully grown on different anaerobic digestates. Highest biomass production (2.15–2.32 g L −1 ) obtained in anaerobic food wastewater. More than 41% of TOC, 84% of NH4 + -N and 70% of TP were effectively removed. The characteristics of wastewater affected algal lipid content and compositions.